2017
DOI: 10.1021/acsami.7b10027
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate–Camptothecin Prodrug Nanoassemblies as a Versatile Nanoplatform for Biomodal Imaging-Guided Self-Active Targeted and Synergistic Chemotherapy

Abstract: "All-in-one" carrier-free-based nano-multi-drug self-delivery system could combine triple advantages of small molecules, nanoscale characteristics, and synergistic combination therapy together. Researches have showed that dual-acting small-molecular methotrexate (MTX) could target and kill the folate-receptor-overexpressing cancer cells. Inspired by this mechanism, a novel collaborative early-phase tumor-selective targeting and late-phase synergistic anticancer approach was developed for the self-assembly of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
80
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(83 citation statements)
references
References 60 publications
(120 reference statements)
3
80
0
Order By: Relevance
“…In addition, as the concentrations of Fe 3 O 4 @BSA‐MTX NPs and pure MTX were increased, their inhibitory effects on tumor cells were significantly increased compared to control group . MTX as a folic acid analog can bind tightly to the dihydrofolate reductase enzyme and lead to disruption of folic acid metabolism and interruption of DNA and RNA synthesis . Therefore, the delivery of sufficient doses of MTX can cause significant toxicity in tumor cells .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, as the concentrations of Fe 3 O 4 @BSA‐MTX NPs and pure MTX were increased, their inhibitory effects on tumor cells were significantly increased compared to control group . MTX as a folic acid analog can bind tightly to the dihydrofolate reductase enzyme and lead to disruption of folic acid metabolism and interruption of DNA and RNA synthesis . Therefore, the delivery of sufficient doses of MTX can cause significant toxicity in tumor cells .…”
Section: Resultsmentioning
confidence: 97%
“…[41] MTX as a folic acid analog can bind tightly to the dihydrofolate reductase enzyme and lead to disruption of folic acid metabolism and interruption of DNA and RNA synthesis. [42] Therefore, the delivery of sufficient doses of MTX can…”
Section: In Vitro Antitumor Activity Of Fe 3 O 4 @Bsa-mtx Npsmentioning
confidence: 99%
“…FA analogs due to the high structural similarity with FA can also be exploited as a tumor‐targeted ligand to recognize FR. For instance, methotrexate (MTX, Food and Drug Administration (FDA)‐approved antimetabolite drug) has been demonstrated with the tumor‐targeting capacity . Li et al have recently reported the targeted delivery of MTX–camptothecin (CPT) prodrug, in which MTX was conducive to FA–receptor‐mediated endocytosis of prodrug .…”
Section: Positive Targetingmentioning
confidence: 99%
“…For instance, methotrexate (MTX, Food and Drug Administration (FDA)‐approved antimetabolite drug) has been demonstrated with the tumor‐targeting capacity . Li et al have recently reported the targeted delivery of MTX–camptothecin (CPT) prodrug, in which MTX was conducive to FA–receptor‐mediated endocytosis of prodrug . In the meanwhile, combination chemotherapy, in vivo near‐infrared (NIR) fluorescence, and photoacoustic dual‐modal imaging are concurrently achieved due to codelivered CPT and MTX and NIR cyanine dye.…”
Section: Positive Targetingmentioning
confidence: 99%
“…The cytotoxicity of MTX-CC-PPT at 72 hw as thought to result from cleavage of carbonic ester owing to the presence of esterasei n tumor cells. [15] Furthermore, cells incubatedw ith free PPT showedt he highest cytotoxicity.I mportantly,o ur prodrug NAs showeda no bviousd ecrease in PPT toxicitya nd provided a controlled drug-releasep rocess. In addition, after the cells were incubatedw ith MTX-SS-PPT NAs and MTX-CC-PPT NAs for 6h,aCalcein-AM/PI Double StainingK it was applied to stain live cells (green)a nd dead cells (red;F igureS16,E SI).…”
mentioning
confidence: 96%